Epoxy-gold nanoparticle nanocomposites with enhanced thermo-mechanical properties: An integrated modelling and experimental study. (12th April 2019) - Demir, Baris; Chan, Kit-Ying; Yang, Dan; Mouritz, Adrian; Lin, Han; Jia, Baohua; Lau, Kin-Tak; Walsh, Tiffany R.
Abstract: In this study, we report an integrated theoretical and experimental investigation of an epoxy polymer matrix containing Au nanoparticles. We performed molecular dynamics simulations to elucidate the atomic-level interactions between the nanoparticles and the epoxy polymer. Our simulation results reveal that the hardener molecules adopted extended conformations on the Au nanoparticle surface, while the epoxy monomer, bisphenol A diglycidyl ether, adopted more complex molecular configurations at the Au interface. The addition of Au nanoparticles into the epoxy polymer increased the glass transition temperature, likely due to the reduced chain flexibility of the polymer matrix. Our predicted and measured mechanical tests suggest that the nanoparticles had a negligible effect on the mechanical properties due to the low concentrations used. Our computational protocol provides a platform to reveal the molecular-level interactions of nanoparticles and thermoset polymers, enabling the future design of multi-functional nanocomposites with superior properties.